1984
DOI: 10.1007/bf01963581
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium constant for calcium ion and ascorbate ion

Abstract: The combination of calcium and ascorbic acid in water at 25 degrees C has been examined by measuring the change of free calcium ion concentration as ascorbate was added in small increment to a solution of calcium. The data show clearly that complex formation between calcium ion and ascorbate ion occurred. At ionic strength mu = 0.1-0.2, the equilibrium constant of Ca++ and the singly-charged ascorbate ion has been measured to be 2.1 M-1. The precision of the result is better than 5% and the accuracy is estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…28 In aqueous solutions, ascorbic acid undergoes ionisation to form singly-and doubly-charged anions, and each of these anionic species may couple with calcium ions to form a complex of the 1:1 type. 17 Such a property can help to reduce the availability of ionic calcium in the presence of a relatively large quantity of ascorbate. This reducing agent interfered with dentin hybridisation when CSE was used (Figs.…”
Section: [ ( ) T D $ F I G ]mentioning
confidence: 99%
See 2 more Smart Citations
“…28 In aqueous solutions, ascorbic acid undergoes ionisation to form singly-and doubly-charged anions, and each of these anionic species may couple with calcium ions to form a complex of the 1:1 type. 17 Such a property can help to reduce the availability of ionic calcium in the presence of a relatively large quantity of ascorbate. This reducing agent interfered with dentin hybridisation when CSE was used (Figs.…”
Section: [ ( ) T D $ F I G ]mentioning
confidence: 99%
“…Two mechanisms may be advocated to explain the stability of this resin-dentin interface: (1) the preservation of collagen integrity promoted by ascorbic acid incorporation. 17 Type I collagen is a major organic component of the dentin matrix and has several important functions. It determines the shape of dentin, and is responsible for anchoring structures bonded to the hybrid layer to the underlying mineralised dentin.…”
Section: [ ( ) T D $ F I G ]mentioning
confidence: 99%
See 1 more Smart Citation
“…32 In our endothelial cell model, millimolar concentrations of ascorbic acid had no effect on basal [ 34 Alternative mechanisms of action of ascorbic acid relate to its reducing and radical scavenger properties. As a reducing agent, ascorbic acid may alter the redox state of soluble guanylyl cyclase in vascular smooth muscle cells, which is sensitized to NO, thus mediating relaxation.…”
Section: Involvement Of Endothelium-dependent Factors In Ascorbic Acimentioning
confidence: 99%
“…Vitamin C, owever, didn't exert a positive effect on femoral BMD and strength. Vitamin C has been reported to stimulate intestinal Ca absorption because of the chelating action of ascorbate with calcium ion (23,24), and Deuchi et al (8) found that, in rats fed a diet containing 5% chi tosan, 1.5% sodium ascorbate supplementation could increase Ca absorption. In the present study, there was no significant difference in Ca absorption between the CH and CHVC groups.…”
Section: Discussionmentioning
confidence: 99%